EFEKTIVITAS TUGAS PRAKTIK BERJUALAN PADA MATA KULIAH KEWIRAUSAHAAN TERHADAP KEMAMPUAN BISNIS MAHASISWA - Nur Jannah Hrp; Sella Aulia; Yulia Novita; Zetri Rahmat (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study examines the effectiveness of sales practice assignments in the Entrepreneurship course on improving students’ business skills. Entrepreneurship learning in higher education often emphasizes theoretical understanding, while many students still experience psychological barriers such as low self-confidence, fear of rejection, and limited ability to apply business concepts in real situations. This research aims to provide empirical evidence on how practical sales activities contribute to the development of students’ entrepreneurial competencies. The study employed a quantitative approach using a pretest–posttest design. The research participants were 40 Economics Education students who were actively involved in sales practice assignments. Data were collected through Likert-scale questionnaires measuring business skills, observation sheets to assess students’ activities during sales practice, and documentation of the learning process. The data were analyzed using a paired t-test to identify differences in students’ business skills before and after the implementation of the sales practice assignment. The findings indicate a significant improvement in students’ understanding of business concepts, communication skills, creativity, and transaction management after participating in the sales practice. Students who were initially shy, passive, or reluctant to engage in entrepreneurial activities demonstrated positive behavioral changes, including increased confidence in offering products, better interaction with customers, and the ability to utilize personal interests or hobbies as potential business opportunities. These results suggest that sales practice assignments provide meaningful experiential learning that bridges theoretical knowledge and real-world application. Therefore, integrating sales practice into entrepreneurship courses is recommended as an effective instructional strategy to enhance students’ business skills and entrepreneurial readiness.